The Impact and Mitigation of Forest Fire for Biodiversity in Indonesia - Ardhana, I Putu Gede (Proceeding International Conference on Global Resource Conservation, 2015)
The purpose of this study was to assess and mitigate the impact of wildfires for biodiversity in Indonesia. Firstly researcher presented information about destruction of forests that spread throughout Indonesia. Forest degradation is caused by failure of government policies in addressing the implementation of concession to investors who were rife on 1967 and concerned this thing, the deforestation system of TPI changed into TPTI, HTI, Joint enterprise, HGU and APL which were caused to decline forest cover. Secondly researcher presented information about forest fires that trigger by the destruction of forests due to deforestation and forest degradation in some areas of concessions and other areas. The collected data has been indicated that forest fires have occurred since 1960 until 2015. These conditions clearly destroy the habitat of flora and fauna that exist in each forest ecosystems. The mitigation that needs to be done is for government to carry out rehabilitation, reforestation, restoration of forest lands where had been burned, so that biodiversity can be recovered, and conservation of germ plasma to be need in each forest ecosystem. The method used in this research was descriptive method by reviewing of regulations and legislation and approach to literature. The study was later described, narrated and in the interpretation and arranged in the form of papers. From these results it can be concluded that the fires is the classic phenomenon that occurs repeatedly and extends preceded by the destruction of forests due to wide spread deforestation and forest degradation in Indonesia.Keywords: biodiversity; degradation and forest fires; impact; mitigation